Avaliação experiencial dos fatores da evasão nos cursos técnicos subsequentes do IFCE, a partir dos gestores do Campus Acaraú - Araújo, Francisco de Assis Magalhães (2020)
This research evaluates the dropout factors of students enrolled in the Subsequent Technical Courses of the Federal Institute of Ceará (IFCE), campus Acaraú, by utilizing the Permanence and Success Plan as one of the policies of the Professional and Technological Education. To this end, it was necessary to appropriate theoretical and methodological contributions of multiple views of the agents and protagonists of this policy in a critical and systematic dimension. The study had the contributions from Cordão (2017), Manfredi (2016), Dore and Lüscher (2011), Pacheco (2011), Bacelar (2003), Vieira (2002), Cunha (2000) and others who were of great importance for the execution of this work. The qualitative research focused on the case study that involved technical high school courses in the subsequent modality of Aquaculture, Fishing, Shipbuilding and Restaurant and Bar Services. Dropping out of school is a very recurrent topic in the educational environment. However, there are not many studies about it regarding the professional Education system in Brazil, and since it conforms to one of the academic performance indicators, the modus operandi related to the figures have attracted the attention of the school staff of the Federal System of Education. The empirical approach took place from 2014 to 2017 and, in order to make sense of the theoretical discussion, it was necessary to start from an evaluation perspective that would contribute to the coherence and conduct of this investigation, which is the reason why the experimental approach by Lejano (2012) was chosen. Among the data collection techniques applied to the school coordinating staff, it was decided to make use of the semi-structured interview and document analysis. The results indicate that the courses have high dropout rates that demand a further study, in addition to the numbers obtained on the Nilo Peçanha and the IFCE em Números Platforms. Three major dropout factors were evidenced in the view of the campus' coordinating staff, which are: the knowledge deficit from elementary education, the absence of transportation, and the inconsistency of the campus academic schedule in relation to that of the municipal and state school systems. In addition to these, others have emerged, most of which are common among the courses investigated. It is also essential that the Permanence and Success Plan as a policy of IFCE be effective and become a routine practice on the campus. It is hoped that this research will support the development of new ways of thinking and acting in the face of Professional and Technological Education and that similar studies will be carried out in the future.